Pengaruh Kualitas Pelayanan Kepuasan Pelanggan Melalui Loyalitas Terhadap Minat Membeli Kembali di Jinan Pet Care and Veterinary Palopo - Khaddapi, Muammar; Burhanuddin; Sapar; Salju; Risal, Muhammad (Jurnal Aplikasi Bisnis dan Manajemen, 2022)
Service quality and customer satisfaction are one of the determining factors for success in business services, including animal health services. The purpose of this study is to explore the dimensions of influence service quality, customer satisfaction through loyalty to repurchase interest at Jinan Pet Care and Veterinary Palopo. In this study, using a quantitative approach. The data collected were 238 clients at Jinan Pet Care and Veterinary Palopo using a structured questionnaire, and the theoretical model was tested using the least partial structured equation modeling (PLS-SEM). The results obtained indicate that the service quality variable, loyalty affects repurchase interest resulting in a significance value of 0.000 < from the value of = 0.05, the customer satisfaction variable does not affect loyalty and repurchase interest produces a significance value of 0.444 > from the value of = 0, 05. Keywords: customer satisfaction, customer loyalty, purchase intentions